Gambaran Kecemasan Praoperasi pada Pasien yang akan Menjalani Operasi Elektif di RSUP Dr. M. Djamil Padang - Ayudita Silvia Hasibuan; Muhammad Zulfadli Syahrul; Gusti Revilla (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: Most patients who will undergo surgery, experience preoperative anxiety. This can affect the patient's condition in various perioperative phases. Even so, preoperative anxiety has not been systematically managed also the information about preoperative anxiety. Objective: This study aims to determine the description of anxiety in patients who will undergo elective surgery at RSUP Dr. M. Djamil padang. Methode: The design of this research is descriptive with cross sectional study. The number of samples in this study were 54 patients who would undergo elective surgery, and were taken using consecutive sampling techniques. Data were collected using The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. Results: We found 44,4% of patients experienced preoperative anxiety according to the results of the APAIS. Conclusion: Based on the results of the study concluded that the majority of patients did not experience preoperative anxiety, both based on the results obtained from the APAIS questionnaire. However, it is hoped that a systematic evaluation and good management of this preoperative anxiety, as part of improving the quality of patient care, especially in the perioperative phase.